Efektivitas manajemen pendidikan karakter dalam upaya meningkatkan prestasi akademik siswa di Sekolah Menengah Kejuruan Negeri 2 Yogyakarta tahun ajaran 2014/2015 - Sri Mulyani; Samsi Haryanto (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aims to determine the effectiveness of character education management in an effort to improve the academic achievement of students in SMK N 2 Yogyakarta, character education management includes planning, organizing, implementing, monitoring and evaluation, support and resistance as well as the efforts made to overcome obstacles. This study used a qualitative research method with a naturalistic approach to data collection. The data collection techniques: interview, observation, study documents. The data source consists of resource person, place and activity as well as related documents to the implementation of education character. Data analysis technique was performed with data reduction, data presentation, and conclusion. Checking the validity of the data is done by extending the observation time, triangulations and auditing. The results showed that the management of character education in SMK N 2 Yogyakarta is quite effective for improving students’ achievement, both academic and non-academic achievement. The average percentage of the graduate student is always higher than 98%, often getting champion level of municipality, provincial and so national. In addition to improving achievement also effectively shape the character of the students as a discipline in complying with school rules, awareness of high worship, no fighting students. All of the mentioned habitual behaviors are an indication of the success of character education. Implementation of the character management received support from the school community and be a flagship program, but is also found in the implementation obstacles that some of the school member s still do not understand the importance of education character so that there are still people who are still violated and less concerned with the implementation of character education. The efforts made by the school to overcome the barriers by doing intensive and sustainable socialization in the school community as well as discipline in enforcing school rules.